CT-guided percutaneous transthoracic needle biopsy of lung lesions - Kocijančič, Igor (Radiology and oncology (Ljubljana), 2007)
Background. In 1883, Leyden described percutaneous lung biopsy, but it was notuntil 1970s that image guided fine needle chest biopsy gained widespread acceptance. Haaga and Alfidi reported CT-guided thoracic biopsy in 1976. Currently, tissue sampling of a thoracic lesion is indicated when the diagnosis is not obtained by the endobronchial technique and when the cytological diagnosis will modify the stage of the disease or influence the therapeutic strategy. Cytology obtained by small-gauge needle aspiration biopsy confirms the nature of the lesion in 80 - 95% of cases and carry a low incidence of major complications according to the literature. The purpose of this retrospective analysis was to provide basic data about diagnostic accuracy and incidence of pneumothorax and chest tube insertion with respect to percutaneous transthoracic CT-guided needle biopsy of lung lesions. Methods. After positioning of the patient we performed a spiral CT of the thorax with the accordingly placed metal mark, which helped us to set the optimal cutaneous entry point. After that we re-checked the localisation of the lesion and marked the entry point with a pen and clean the surface to keepit sterile. After we applied local anaesthetic subcutaneously, we used coaxial 18G Gallini aspiration biopsy needles with cutting tip for CT- guided aspiration cytologic examination. The length of the needle was chosen according to the distance of the targeted lesion. Results. From January 2005 to January 2007 forty-three patients - 24 men and 19 women who were 26-79 years old (mean +/- SD, 59.8 +/- 10 years) were referred to the Institute of Radiology to undergo the PTNB. One patient was referred twice. Consequently, the hospital records and images of 44 consecutive cases of percutaneous transthoracic fine needle aspiration biopsy procedure were retrospectively analysed. (Abstract truncated at 2000 characters)
Keywords: biopsija; Biopsija igelna; Biopsy, Needle; diagnostika; Lung Neoplasms; novotvorbe; Pathology; pljučne bolezni; Pljučne novotvorbe; Pneumothorax; Pnevmotoraks; Tomografija radiografska, računalniška; Tomography, X-Ray Computed